Evolution and development of the alpaca breeds: Suri and Huacaya - Bustinza Choque, A. Víctor (2021)
This review is based on the publication «Definition of breeds of alpacas and llamas», by Animal Genetic Resources journal, which places the alpaca at the primary level in the evolution of domestic animal breeds. and makes a review of the domestication of the alpaca, the treatment received during the conquest and colonialism, the inclusion of the alpaca fibre in the international textile market, the technical management during the Republic until the present, first in large farms (haciendas), then in the associative companies and currently in medium-sized properties and in State institutions and universities. Management testimonies are also presented with figures from some producers and finally the morphological differential characters and the fibre structure that characterizes and defines the Suri and Huacaya breeds.